The Influence of Emotional Intelligence, Spiritual and Intellectual on Students’ Ethical Behavior - Enos Lolang; Najamuddin Petta Solong; Holdin Sagita; Didik Supriyanto; Firman Aziz (Departement of Mathematics Education, 2023)
The purpose of this research is to find out how emotional intelligence, intellectual intelligence and spiritual intelligence affect students' ethical behavior during the learning process. This research uses a quantitative approach with descriptive methods. Quantitative can be interpreted as a research method based on the philosophy of positivism, used to examine certain populations or samples, collecting data using research instruments, analyzing data is quantitative / statistical, with the aim of testing established hypotheses. Descriptive method is research conducted to find out about the independent variable, either one or more variables, without making comparisons and connecting one to another. In this study the researchers aimed to obtain information about emotional intelligence, intellectual intelligence, and spiritual intelligence on students' ethical behavior. There is a positive influence of emotional intelligence on students' ethical behavior during the learning process. This is evidenced by the results of the T test on the variable emotional intelligence (X1) and it is found that t-count > t-table (3.423> 2.048) with a significance value <0.05 (0.002 <0.05). There is a positive influence of intellectual intelligence on students' ethical behavior during the learning process. This is evidenced by the results of the T-test on the intellectual intelligence variable (X2) obtained that tcount > t-table (3.023>2.048) with a significance value <0.05 (0.005<0.05). There is a negative influence of spiritual intelligence on students' ethical behavior during the learning process.